Diffusion tensor magnetic resonance imaging in very early onset pediatric multiple sclerosis. (April 2016) - Rocca, MA; Sonkin, M; Copetti, M; Pagani, E; Arnold, DL; Narayanan, S; Sled, JG; Banwell, B; Filippi, M
Objectives: Active myelination during childhood may influence the impact of multiple sclerosis (MS) on brain structural integrity. We studied normal-appearing white matter (NAWM) in children with MS onset before age 12 years using diffusion tensor (DT) magnetic resonance imaging (MRI). Methods: DT MRI scans were obtained from 22 MS children with their first attack before age 12 years, and 31 healthy controls from two referral centers. Using probabilistic tractography, brain tissue integrity within interhemispheric, intrahemispheric, and projection tracts was compared between patients and site-matched controls. The impact of disease and age at MRI on tract NAWM fractional anisotropy (FA) and mean diffusivity (MD) values was evaluated using linear models. Results: Compared to controls, pediatric MS patients had reduced FA and increased MD of the bilateral superior longitudinal fasciculus and corpus callosum (CC), without center-by-group interaction. CC NAWM average FA was correlated with brain T2 lesion volume. In controls, the majority of the tracts analyzed showed a significant increase of FA and decrease of MD with age. Such a linear correlation was lost in patients. Conclusions: In very young pediatric MS patients, DT MRI abnormalities affect brain WM tracts differentially, and are only partially correlated with focal WM lesions. Impaired maturation of WM tracts with age may be an additional factor contributing to these findings.